(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Isworo S, Oetari PS. 2022. Flora and fauna in the areas around artisanal gold mining in Selogiri Sub-district, Wonogiri, Indonesia. Biodiversitas 23: 6600-6618. Artisanal or small-scale gold mining has devastating impacts on the environment due to negligence of the principles of good environmental management. In particular, the mining activities often involve vegetation clearing and topsoil removal, which affect the biotic elements of the mined landscape. Selogiri Sub-district, Wonogiri District, Central Java Province, has a gold mineral resource that drives many traditional mining activities that have an indirect impact on the ecosystem’s species diversity and community structure. This research aimed to investigate the diversity of flora and fauna in Selogiri Sub-district by comparing the area where the artisanal gold mining occurred (the inside area) and the areas surrounding the mining (the outside area). Six groups of taxa were observed in this study, including the plant group using the plot method, avifauna (birds) using Indices Ponctuels d’Abondance method, Odonata (dragonflies) and Lepidoptera (butterflies) both using visual encountering survey (VES) method, micromammals (Rodentia) using traps, VES, and camera traps and herpetofauna (amphibians and reptiles) using VES method. The diversity values of each taxa group in the inside and outside area were calculated and Sorensen’s Coefficient Similarity Index formula was analyzed to see the community similarity between the two areas. A total of 243 species were found, consisting of Lepidoptera (35%), flora taxa (29%), avifauna (16%), herpetofauna (9%), Odonata (7%), and mammals (3%). The avifauna and Odonata had higher diversity values in the outside area than in the inside area. Similarly, the outside area had a higher diversity value for mammalian taxa documented using the VES method. Meanwhile, using the trap method, the taxa of Lepidoptera, herpetofauna, and mammals had higher diversity value in the inside area than in the outside. Nonetheless, the two areas had moderate similarity in the composition of flora and fauna species, with a community similarity value of less than 60% for all taxa studied. Conservation activities and off-site tree planting are solutions for restoring ecosystem structure and function to support ecological stability and biodiversity.